Development of the Lunate‐Shaped Caudal Fin in White Shark Embryos. Issue 6 (22nd January 2018) - Tomita, Taketeru; Toda, Minoru; Miyamoto, Kei; Oka, Shin‐Ichiro; Ueda, Keiichi; Sato, Keiichi
ABSTRACT: The lunate‐shaped caudal fin in lamnid sharks is a morphological specialization for their thunniform mode of locomotion, but its developmental process during gestation has been poorly investigated. Observations of 21 embryonic specimens of the white shark ( Carcharodon carcharias ) revealed that their caudal fin morphology drastically changes from strongly heterocercal to lunate‐shaped through ontogeny. This morphological change involves (1) rapid elongation of the ventral lobe, (2) increased upward curvature of the vertebra within the caudal fin, and (3) formation of keels at both lateral sides of the caudal fin base. These morphological changes are probably shared among the members of the family Lamnidae and are in contrast with the developmental process of the heterocercal tail in the lamniform Carcharias taurus, in which the caudal fin morphology is almost unchanged through the late gestation period. Anat Rec, 301:1068–1073, 2018. © 2018 Wiley Periodicals, Inc.